Agenda Good Governance dan Globalisasi Ekonomi: Suatu Tinjauan Kritis - Budi Winarno (Universitas Muhammadiyah Yogyakarta, 2013)
As a concept, development and good governance are not neutral, but they bring domination and interest. Currently, in era of globalization, there is a trend that shows democratization and the agenda of good governance are suspected to become a neoliberal project aimed to strengthen the domination of market over the state. Therefore, in order to prevent the agenda of good governance serving the interest of global corporations, democracy should be able to guarantee the individual rights, and the government continuously plays its crucial role in pushing the realization of social justice. In the context of maintaining democracy and civil society, the agenda of good governance are not only implemented by public institutions, but also they are done by both global corporations and global governance institutions.